Expressive cartographic sessions as a methodology for territorial research in pandemic and emergency: the case of the neighbourhoods of Chorrillos and Santa Inés in Viña del Mar - Catalán Catalán, Mario; Toledo Valenzuela, Yerko; Giusto Unzaga, Flavia (Universidad Pedagógica y Tecnológica de Colombia, 2024)
This work aims to report on a methodological proposal for territorial research in the context of a pandemic and emergency, which has been called “expressive cartographic days” (JCE), which is understood in this study as a situated form of social cartography that seeks account for the intersubjective expressivity of people from the centrality of the particular territory that is inhabited in relation to a social phenomenon such as the covid-19 pandemic. This proposal is the product of an investigation that analyses the strategies and tactics of managing the pandemic in the city of Viña del Mar, developed between the years 2021 and 2022 in the Santa Inés and Chorrillos neighbourhoods, in which social leaders, professionals from health centres and the Illustrious Municipality of Viña del Mar. The research process is reported, as well as the facilitators and obstacles; The methodological process of the expressive cartographic sessions and the information produced associated with the actions developed in relation to the strategies deployed by the local government, and also the self-managed tactics emerged from community organizations, are detailed. The results of these reflections allow us to demonstrate the contributions of the cartographic profession in territorial research to make visible the intersubjectivity of the inhabitants in socio-territorial phenomena in contexts of crisis and emergency.